Pembuatan Desain Kemasan Produk Inovasi di Kelurahan Benjala, Kecamatan Bonto Bahari Kabupaten Bulukumba - Nurul Ainun Pratiwi Mas'ud; Ilham Jaya (Universitas Hasanuddin, 2023)
Packaging is a container that is used to protect products, marketing tools, building brand identity, and attract buyers so as to increase sales. This packaging design was created to maintain product quality and in order to increase the attractiveness of the products developed by Hasanuddin University KKNT 109 students in Benjala ward. The creation process of this product packaging design begins with design making on January 14, 2023, until the packaging manufacturing process on January 20, 2023, and it continues with a product design and packaging presentation to the Benjala ward community on January 26, 2022. The modelling of this product packaging design is expected to be an inspiration and also to stimulate the community to continue their innovation in empowering local products and increasing the economic activities of the people in the Benjala ward.